Between Shadows and Knowledge: Doing Sociology in Time of War - Dias, Gustavo (Italian Sociological Review, 2025)
Book review of Amín Pérez (2023), Bourdieu & Sayad Against Empire: forging Sociology in Anticolonial Struggle. Cambridge: Polity Press.